In Situ Investigation of the Thermal Decomposition of Cl4(CH3CN)W(NiPr) During Simulated Chemical Vapor Deposition. Issue 32 (5th July 2019) - Nolan, Michelle M.; Kim, Seo Young; Koley, Arijit; Anderson, Tim; McElwee‐White, Lisa
Abstract : Design of precursors for thin film growth by chemical vapor deposition (CVD) can be informed by knowledge of the precursor decomposition mechanism. However, the vast majority of decomposition characterization is done by techniques that do not capture CVD conditions. This work used a custom CVD reactor with in situ Raman spectroscopy capabilities to investigate the gas phase thermal decomposition of the tungsten imido complex Cl4 (CH3 CN)WN i Pr, a known precursor for the aerosol‐assisted (AA)CVD of tungsten carbonitride thin films. In combination with previous computational and ex situ data, we propose a decomposition mechanism for this precursor under CVD conditions, based on observation of gas phase products of N(imido)‐C bond homolysis and σ ‐bond metathesis between the precursor W–Cl bond and H2 . Abstract : A look inside CVD: Most characterization of chemical vapor deposition (CVD) precursors occurs under conditions different than those inside CVD reactors. This work used in situ Raman spectroscopy during simulated CVD to examine the gas phase decomposition of a known WN x C y precursor. We now propose a decomposition mechanism for the tungsten imido complex Cl4 (CH3 CN)WN i Pr during CVD.